Analysis of Student Difficulties in Solving Questions Newton’s Law of Motion at State SMAN 1 Ranah Batahan - Ronita, Ade; Putra, Amali (Universitas Negeri Padang, 2024)
The results of the documentation analysis of physics learning outcomes for students of class X SMAN 1 Ranah Batahan, showed that student learning outcomes on Newton's law of motion material occupied the lowest value compared to other materials. That is, students have difficulty in solving problems related to Newton's laws of motion. This study aims to a) Knowing how the tendency of students' difficulties in solving Newton's law of motion material problems at SMA Negeri 1 Ranah Batahan, b) Knowing the factors of difficulty experienced by students in solving Newton's law material questions about motion in SMA Negeri 1 Ranah Batahan, c) Knowing how the teacher's learning strategy on Newton's law of motion at SMA Negeri 1 Ranah Batahan. This research is included in the type of descriptive research with a qualitative approach. The research sample was taken usiing the Stratified Random Sampling technique. The number of samples obtained is 27 students who represent students with high, medium and low grades and physics teachers who teach at schools. Research data about students' difficulties in solving problems were obtained through 10 questions about Newton's law of motion, data on student difficulty factors and teacher learning strategies were obtained using a questionnaire. The research instrument used has met the feasibility through a validation test by 3 validator lecturers. Data processing is done through the percentage technique. The results showed that a) The tendency of students' difficulties in Newton's law of motion was in the category of high difficulty with a percentage value of 67%, b) Factors causing student difficulties in terms of internal factors were health factors of 58%, interest factors of 48%, talent by 44%, motivation factor by 46%, and habit factor by 48%. Judging from the external factors include the teacher factor with a score of 57%, environmental factors by 40%, and the characteristics of the subject matter of 48%. This percentage figure shows that these factors are low to be the cause of students' difficulties in solving problems, and c) The teacher's learning strategy on Newton's law of motion is in moderate criteria. In general, the teacher has not finished instilling the important concepts needed in discussing Newton's laws of motion..